The reliability of back-extrapolation in estimating V˙O2peak in different swimming performances at the severe-intensity domain - Massini, Danilo Alexandre [UNESP]; Simionato, Astor Reis [UNESP]; Almeida, Tiago André Freire [UNESP]; Macedo, Anderson Geremias [UNESP]; Espada, Mário Cunha; Reis, Joana Filipa; Besone Alves, Francisco; Pessôa Filho, Dalton Müller [UNESP] (Frontiers, 2022)
The amount of anerobic energy released during exercise might modify the initial phase of oxygen recovery (fast-O2debt) post-exercise. Therefore, the present study aimed to analyze the reliability of peak oxygen uptake (Formula presented.) estimate by back-extrapolation (Formula presented.) under different swimming conditions in the severe-intensity domain, verifying how the alterations of the (Formula presented.) recovery profile and anerobic energy demand might affect (Formula presented.) values. Twenty swimmers (16.7 ± 2.4 years, 173.5 ± 10.2 cm, and 66.4 ± 10.6 kg) performed an incremental intermittent step protocol (IIST: 6 × 250 plus 1 × 200 m, IIST_v200m) for the assessment of (Formula presented.). The (Formula presented.) off-kinetics used a bi-exponential model to discriminate primary amplitude, time delay, and time constant (A1off, TD1off, and τoff) for assessment of fast-O2debt post IIST_v200m, 200-m single-trial (v200 m), and rest-to-work transition at 90% delta (v90%Δ) tests. The linear regression estimated (Formula presented.) and the rate of (Formula presented.) recovery (BE-slope) post each swimming performance. The ANOVA (Sidak as post hoc) compared (Formula presented.) to the estimates of (Formula presented.) in v200 m, IIST_v200 m, and v90%Δ, and the coefficient of dispersion (R2) analyzed the association between tests. The values of (Formula presented.) during IIST did not differ from (Formula presented.) in v200 m, IIST_v200 m, and v90%Δ (55.7 ± 7.1 vs. 53.7 ± 8.2 vs. 56.3 ± 8.2 vs. 54.1 ± 9.1 ml kg−1 min−1, p > 0.05, respectively). However, the (Formula presented.) variance is moderately explained by (Formula presented.) only in IIST_v200 m and v90%Δ (RAdj2 = 0.44 and RAdj2 = 0.43, p < 0.01). The TD1off and τoff responses post IIST_v200 m were considerably lower than those in both v200 m (6.1 ± 3.8 and 33.0 ± 9.5 s vs. 10.9 ± 3.5 and 47.7 ± 7.9 s; p < 0.05) and v90%Δ (10.1 ± 3.8 and 44.3 ± 6.3 s, p < 0.05). The BE-slope post IIST_v200m was faster than in v200 m and v90%Δ (-47.9 ± 14.6 vs. -33.0 ± 10.4 vs. -33.6 ± 13.8 ml kg−1, p < 0.01), and the total anerobic (AnaerTotal) demand was lower in IIST_v200 m (37.4 ± 9.4 ml kg−1) than in 200 m and 90%Δ (51.4 ± 9.4 and 46.2 ± 7.7 ml kg−1, p < 0.01). Finally, the τ1off was related to AnaerTotal in IIST_v200m, v200 m, and v90%Δ (r = 0.64, r = 0.61, and r = 0.64, p < 0.01). The initial phase of the (Formula presented.) recovery profile provided different (although reliable) conditions for the estimate of (Formula presented.) with BE procedures, which accounted for the moderate effect of anerobic release on (Formula presented.) off-kinetics, but compromised exceptionally the (Formula presented.) estimate in the 200-m single trial.
Keywords: back-extrapolation; oxygen uptake kinetics; oxygen uptake recovery; peak oxygen uptake; swimming